KOLABORASI SEKOLAH DAN INDUSTRI: PEMBELAJARAN BERBASIS PROYEK TERINTEGRASI INDUSTRI (PjBL-T) - Fransiska Dwi Yunitasari; Nuniek Herdyastuti; Achmad Imam Agung (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
Collaboration between vocational schools and industry in PjBL-T is important in supporting contextual learning that is relevant to the world of work. The aim of this research was to provide insight and implementation steps in PjBL-T at SMKN 1 Driyorejo , as well as practical guidance for vocational schools and industry in preparing graduates who are competent and ready to compete. This research used a qualitative approach with descriptive research and case studies. Research subjects were determined using purposive sampling and snowball sampling techniques, which included school principals, deputy principals, productive subject teachers, as well as industry parties. Data were collected through document review, direct observation at school, and in-depth interviews. The success of PjBL-T depends on collaboration between productive teachers and industry. Implementation of PjBL-T includes four main stages: 1) preparation of project planning, 2) project implementation, 3) evaluation of project results, and 4) marketing of project products. PjBL-T integrates schools with industry to improve student competency through real experience in producing and marketing products according to industry standards.